Contamination of Southern Iraq Waterways - Al-Imarah, Faris J.M.; Abdul-Nabi‎, Zuhair A.; Hantoush‎, Abbas A.; Al-Anber, Luma J.M.; Hayder, Mahmood Sh. (Mesopotamian Journal of Marine Sciences, 2023)
In this study a certain chemical elements Cu, Mn and Pb were ‎determined in water, and another set of Cd, Cu, Fe, and Zn were ‎determined in sediments from selected sites (1) Qurnah, (2) Al-‎Noor Bridge, (3) Saad Bridge, (4) Sindbad Island, (5) Al-Ashar, ‎‎(6) Abu Al-Khaseeb, (7) Seebah, and (8) Al-Faw along the ‎Southern Iraqi water ways during the year 2015. Low levels of ‎heavy metals were recorded in the water of Shatt Al-Arab river, ‎they were in the range 0.00735 - 0.02090, 0.00505 - 0.02145, ‎and 0.00150 - 0.0837 µg/l for Cu, Mn, and Pb respectively, and ‎lower values recorded were for the toxic Pb metal. On the other ‎hand levels of heavy metals in the sediments were little bit high ‎and in the range 0.1172488 - 0.614806, 17.175343 - 40.156639, ‎‎8156.970 - 21021.63, and 31.864781 - 79.160779 µg/g dry ‎weight for Cd, Cu, Fe, and Zn respectively. Fe recorded the ‎highest levels of heavy metals in all sites due to the nature of the ‎sedimentary valley in Iraq. Low levels of heavy metals Cu, Fe, ‎and Zn were recorded in the sediments of Seebah (site no.7) due ‎to the effect of sediment movements through Karun River from ‎the Iranian territories. More over levels of all investigated heavy ‎metals were recorded high values in the water from Ashar (site 5) ‎due to corrosion of marine vessels sunk in the area since the Iraqi-‎Iranian War 1980-1988.‎